Análise dos fatores que influenciam a decisão de compra de veículos elétricos no Brasil - Schvartz, Marceli Adriane (2024)
Technological advancement has driven growth in the global economy, but has also resulted in high rates of polluting emissions, highlighting the urgency of environmental issues. The transportation sector, especially the increase in individual vehicle ownership, contributes significantly to air pollution. Brazil, with its high number of individual motor vehicles, faces growing challenges in this context. The transition to electric vehicles (EVs) is seen as a sustainable alternative to reduce emissions of polluting gases. However, in Brazil, the EV market has not yet reached significant numbers. Given this scenario, this study aims to analyze the factors that influence the decision to buy EVs in Brazil, highlighting personal, psychological, economic, performance and environmental variables and the barriers perceived by consumers. The aim is also to develop a model with guidelines that can help stakeholders. As for the method, the research comprises two phases. The first, characterized as qualitative, was conducted through a systematic literature review in the Web of Science, Scopus and Science Direct databases. This process resulted in the selection of 430 final papers, the results of which made it possible to identify the factors and variables that can influence consumers' decision to buy EVs. Based on these results, a questionnaire was drawn up to assess experts' perceptions. The next stage of the study, characterized as quantitative, involved a survey of 514 respondents. Measurement was carried out using statistical procedures and Structural Equations. The main results obtained in the survey revealed a trend among the participants, indicating that, in the Brazilian context, decision-making for the purchase of EVs is primarily influenced by performance factors. This finding highlights the importance attributed by consumers to autonomy, recharging locations and maintenance. It was also observed that economic factors play a significant role in the decision to buy EVs. This suggests that although performance is a priority, consumers are sensitive to financial considerations such as acquisition costs, maintenance and long-term savings. With regard to psychological, economic, performance and environmental factors, variables such as safety (63.42%), long-term savings (55.84%), battery performance (55.84%) and pollution reduction (46.50%) stood out, respectively. At the end, potential guidelines were discussed considering the study's success variables.